A Study of Impact of Behavioural Factors on ESG Investment - Upadhyaya, Dr. Charu; Khan, Dr. Shebazbano; Sandanshive, Dr. Vishal; Awasthi, Mr. Gunwant (The journal of contemporary issues in business and government, 2023)
Purpose of the Study: The main aim of the study is to analyze the behavioural factors affecting ESG investments in India. Methodology: The study is based on primary data. Data is collected through a well- structured questionnaire. The respondents are drawn by means of convenient sampling method. The sample of 219 Respondents was collected for the study. Findings: It is found that the Behavioral aspect is dependent on ESG factors. Practical Implications: Through this study, it is expected to get significant result and suggestions which could benefit the investors. Originality / Value: To the best of the authors’ knowledge, this manuscript is the only research which uses the Regression Model with reference to ESG in India.